2020
DOI: 10.1016/j.jid.2019.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Responses to the TYK2/JAK1 Inhibitor PF-06700841 Reveal Reduction of Skin Inflammation in Plaque Psoriasis

Abstract: The IL-23/T helper type 17 cell axis is a target for psoriasis. The TYK2/Janus kinase 1 inhibitor PF-06700841 will directly suppress TYK2-dependent IL-12 and IL-23 signaling and Janus kinase 1edependent signaling in cells expressing these signaling molecules, including T cells and keratinocytes. This clinical study sought to define the inflammatory gene and cellular pathways through which PF-06700841 improves the clinical manifestations of psoriasis. Patients (n ¼ 30) with moderate-to-severe psoriasis were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…BMS-986165 is a selective Tyk2 inhibitor that have shown efficacy in a Phase II clinical trial for psoriasis treatment [80] (Table 1), and it is being studied in systemic lupus erythematosus, psoriatic arthritis, and inflammatory bowel diseases. Brepocitinib (PF-06700841) is a Tyk2/Jak1 inhibitor that is being tested in psoriasis [81] (Table 1). Interestingly, the efficacy of topical treatments with Jakinibs is being examined in clinical trials for treatment of dermatological disorders [82].…”
Section: Il-23 Proximal Signaling Cascade: Jaks/stats Modulementioning
confidence: 99%
“…BMS-986165 is a selective Tyk2 inhibitor that have shown efficacy in a Phase II clinical trial for psoriasis treatment [80] (Table 1), and it is being studied in systemic lupus erythematosus, psoriatic arthritis, and inflammatory bowel diseases. Brepocitinib (PF-06700841) is a Tyk2/Jak1 inhibitor that is being tested in psoriasis [81] (Table 1). Interestingly, the efficacy of topical treatments with Jakinibs is being examined in clinical trials for treatment of dermatological disorders [82].…”
Section: Il-23 Proximal Signaling Cascade: Jaks/stats Modulementioning
confidence: 99%
“…Brepocitinib, which was formerly known as PF-06700841, is currently under investigation for several autoimmune indications [ 74 ]. It is known to directly inhibit TYK2-dependent IL-12, IL-23 signalling and JAK2 dependent signalling, which includes T-cells and keratinocytes [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, JAK1 activity is positively correlated with Ki-67 expression. 40,41 Therefore, we investigated whether Anwulignan could inhibit Ki-67 expression in NSCLC tumour tissues. Results indicated that Anwulignan strongly reduced the Ki-67 expression ( Figure 6E).…”
Section: Discussionmentioning
confidence: 99%